PENGARUH SLOW DEEP BREATHING TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI - Rizki Sari Utami Muchtar; Siska Natalia; Livatasia Patty (LPPM Universitas Abdurrab, 2022)
Hypertension is known as a major health problem worldwide that causes various life- threatening heart diseases. The Department of Health Household Survey on Health shows that hypertension is ranked first as the most common degenerative disease. The phenomenon found in the work area of the Tiban Baru Health Center in Batam City was 150 people. This study was conducted to determine the effect of the Slow Deep Breathing Technique on Blood Pressure Reduction in Hypertension Patients in the Work Area of the Tiban Baru Health Center, Batam City . The research method was Quasy Experimental Design, with pretest-posttest with control group. The sample consisted of 30 respondents consisting of 15 respondents from the intervention group and 15 control groups who suffered from hypertension in the Work Area of the Tiban Baru Health Center, Batam City , with the sampling technique of purposive sampling. The data was processed using the Wilcoxon test. The results showed that the systolic blood pressure of the intervention group before being treated was 165.67 mmHg and diastolic 94.73 mmHg and the systolic blood pressure of the intervention group after being treated was 155.33 mmHg and diastolic 88.00 mmHg. Based on the characteristics of the respondents, the most age was >45 years (80%), and the most gender (73.3%) were women. The results showed that the p-value was 0.002 (<0.05). It was concluded that there was an effect of slow deep breathing on decreasing blood pressure. It is expected that people with hypertension can apply slow deep breathing therapy to lower blood pressure to avoid complications of hypertension.